2004
DOI: 10.1088/0268-1242/19/6/008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of strained Si/SiGe material for high performance CMOS

Abstract: The enhanced electrical performance of dual quantum well strained Si/SiGe n-channel MOSFETs has been investigated as a function of SiGe material quality. The higher electron mobility in strained Si compared with bulk Si has been translated into performance gains in terms of device transconductance and on-state drain current exceeding 120% compared with simultaneously fabricated Si controls. Increased performance was demonstrated for a wide range of gate lengths and operating conditions. Trade-offs between opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Strained Si n-MOSFETs were fabricated on relaxed SiGe virtual substrates using a conventional process described previously. 12 The virtual substrates were grown by low-pressure chemical vapor deposition. Devices had 6 nm thermally grown gate oxides, determined by capacitancevoltage measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strained Si n-MOSFETs were fabricated on relaxed SiGe virtual substrates using a conventional process described previously. 12 The virtual substrates were grown by low-pressure chemical vapor deposition. Devices had 6 nm thermally grown gate oxides, determined by capacitancevoltage measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Another challenge for globally strained Si/ SiGe MOSFETs is material quality, since epitaxial growth of strained layers on relaxed virtual substrates leads to surface roughness, 10,11 which can impact photolithography in addition to gate oxide quality. 12 High quality gate dielectrics are paramount if MOSFETs with high performance and good reliability are to be realized. Ge outdiffusion from a SiGe virtual substrate or a SiGe source/drain stressor during high thermal budget processing can degrade gate oxide interface quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of electrons this effect has been clearly shown from mobility measurement and calculation in SiGe-Si-SiGe quantum wells [2][3][4] and it has been used for designing high-performance MODFET with low noise figure and high cut-off and maximum oscillation frequencies [5][6]. Now efforts are made to transfer this advantage in CMOS technology on either bulk or insulating substrate [7][8][9][10]. It has been demonstrated that the effective electron mobility in MOS structures can be substantially enhanced using tensile strained-Si channel grown on SiGe buffer layer [7,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…A compositionally graded layer to confine threading dislocations was grown by gradually accommodating the lattice mismatch between Si 1−x Ge x layers [12,13] on (1 0 0) silicon substrate via molecular beam epitaxy (MBE) in which the growth condition was shown in [14,15]. A 630 nm thick layer of the fully relaxed Si 0.7 Ge 0.3 was grown on top of the graded layer, followed by a 50 nm strained Si-capping layer.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…In contrast to the misfit dislocations, the threading dislocations primarily arise from the dislocated substrate/buffer layer and dislocation loops nucleated from the step edgy [11]. Therefore, the threading dislocation density can be reduced by alternative growth methods, such as an introduction of a graded buffer layer used in our study [12,13]. These misfit/threading dislocations are primarily observed using transmission electron microscopy (TEM), which, unfortunately, has disadvantages such as complex and destructive sample preparation and it is time consuming.…”
Section: Introductionmentioning
confidence: 99%